ANALYSIS OF THE IMPACT OF USING CHATGPT ON IMPROVING STUDENTS' CRITICAL THINKING ABILITIES - Yansen P. Sitanggang; Rafika Bayu Kusumandari; Decky Avrilianda (RADJA PUBLIKA, 2026)
The development of information technology has brought significant changes to the world of education, particularly through the application of Artificial Intelligence (AI) to improve the quality of learning. One example of this application is ChatGPT, an AI platform capable of providing instant feedback in text-based interactions. Technology integration is considered to have significant potential in stimulating students' critical thinking skills. This study aims to analyze the impact of ChatGPT use on improving students' critical thinking skills in learning activities. This study used a literature review method by reviewing various literature relevant to the research. The results showed that the use of ChatGPT optimizes the speed of information acquisition. However, in reality, ChatGPT answers tend to be correct, so students believe them implicitly without critical review. This decline in cognitive engagement cumulatively results in a decline in critical thinking skills due to technology dependence. Therefore, the use of ChatGPT in learning needs to be wisely directed by educators so that it can become an effective supporting tool in improving students' critical thinking skills. The appropriate integration of AI technology in learning is expected to encourage the creation of a learning process oriented towards the development of critical thinking skills.